User Experience Analysis on Facebook Marketplace Pekanbaru using User Experience Questioner Method (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The integration of e-commerce features into social media platforms has created unique user experience challenges, particularly in localized buying and selling communities. This study evaluates the user experience of Facebook Marketplace within the Pekanbaru Jual Beli Online (PJBO) community using the User Experience Questionnaire (UEQ) method. Through a quantitative approach with 400 active users selected via simple random sampling, this research reveals significant user experience gaps in a platform that accommodates over 136,000 members. The results demonstrate that four core UX dimensions fall below industry benchmarks: attractiveness (0.85), clarity (0.81), efficiency (0.82), and dependability (0.79), all with narrow confidence intervals (±0.14-0.18), indicating consistent user dissatisfaction across these dimensions. While stimulation (0.80) achieved "good" ratings and novelty (0.78) scored "above average," the overall UX profile reveals a platform that provides adequate innovative features but struggles with fundamental usability aspects. This study contributes to UX literature by examining the unique intersection of social network-based e-commerce in localized Indonesian markets, and provides platform developers with actionable recommendations to enhance system navigation, transaction efficiency, and trust mechanisms. However, this study employs only the UEQ method and does not extend to a more comprehensive evaluation, such as assessing system effectiveness and application interface performance.